Moufang Loop of Odd Order pq4r3 and Associator Subloop of Odd Order r2 - Joel, Emmanuel; Adewoye Ademola, Lois (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Under the condition that , with , where and are distinct odd primes, Moufang loops of order ⁴³ has been shown to be associative (Rajah & Ademola, 2017). In this paper, we searched through the unique characteristics of Moufang loop of odd order ⁴³ and it’s associator subloop of odd order ² under the conditions that and be odd primes with and . This paper has also shown that Moufang Loop of odd order 43 cannot have an associator subloop of odd order .